PERFORMANCE OF THE CIS HIGHER EDUCATION INSTITUTIONS IN THE GLOBAL WEBOMETRIC RANKING BY INSTITUTIONAL PROFILE - Sergey V. Ablameyko; Mikhail A. Zhuravkov; Viktor V. Samokhval (Moscow Polytechnic University, 2022)
In the past decade, rankings have become significant tools for improving the quality of teaching,learning, and research, and also important vehicles for promoting competitiveness of higher education institutions (HEIs) in the global educational markets. This paper shows the performance in the webometric ranking by a selection of Belarusian higher education institutions of six different profiles (classical, education, medical, technical, agricultural, and economics), and compares this to the performance of comparable HEIs of similar profiles in the CIS. A list of the top ten HEIs in the CIS is presented, along with the positions in the webometric ranking of various institutions worldwide among the top one hundred HEIs grouped by profile. The positions of the CIS institutions are highlighted in these listings.